Association Between Neutrophil to Lymphocyte Ratio and Severity of Coronary Artery Disease. (January 2014) - Kaya, Hasan; Ertaş, Faruk; İslamoğlu, Yahya and Kaya, Zekeriya and Atılgan, Zuhal Arıtürk and Çil, Habib and Çalışkan, Ahmet and Aydın, Mesut and Oylumlu, Mustafa and Soydinç, Mehmet Serdar
The aim of this study is to investigate the association between neutrophil to lymphocyte ratio (NLR) and severity of coronary atherosclerosis. A total of 172 patients undergoing coronary angiography were included in the study. Control group consisted of patients with normal coronary arteries. Patients with coronary stenosis were divided into 2 groups by use of Gensini scores. The NLR was higher in severe atherosclerosis group compared with mild atherosclerosis and control groups ( P < .001). In correlation analysis, NLR showed significant correlation with Gensini score. A cutoff value of 2.5 for NLR predicted severe atherosclerosis with a sensitivity and specificity of 62% and 69%, respectively. After multivariate analysis, high levels of NLR were independent predictors of severe atherosclerosis together with glucose and high-density lipoprotein. Our study suggests that the NLR is a predictor of severe atherosclerosis that may be useful for cardiac risk stratification in patients with coronary artery disease.